Social Behavior of River Bank Communities in Banua Anyar - Lydia Lasprita; Bambang Subiyakto; Jumriani Jumriani; Rusmaniah Rusmaniah; Muhammad Adhitya Hidayat Putra (The Innovation of Social Studies Journal, 2023)
Humans and the natural environment cannot be separated from one another who need each other. Human behavior greatly influences changes in the surrounding environment that have excellent or negative impacts. In the article, the researcher aims to describe the social behavior of the riverbank community in Banua Anyar Village. The social behavior of the riverbanks in Banua Anyar Sub-District is that the riverbank people have always used river water for their daily needs; in the riverbank, people who live in Banua Anyar Village do not use river water for drinking water. The method used in this research is the qualitative method. Data collection through in-depth interviews, observation, and documentation. Data analysis through the stages of reduction, presentation, and drawing concludingly verified. So there are some social behaviors of the riverbank community in Banua Anyar Village occur; the riverbank community carries out routine religious activities, throws garbage and waste directly into the river, the community still uses river water for bathing, washing, toilets (MCK), and there are cages floating nets in the river environment. The social behavior of the riverbank community in Banua Anyar Village occurs in four forms of social behavior as follows, 1. Instrumental Rational Actions, 2. Value Rationality Actions, 3. Traditional Actions, and 4. Effective Actions.